Matrix Metalloproteinase in Abdominal Aortic Aneurysm and Aortic Dissection - Eithne M. Maguire; Stuart W. A. Pearce; Rui Xiao; Aung Y. Oo; Qingzhong Xiao (MDPI AG, 2019)
Abdominal Aortic Aneurysm (AAA) affects 4-5% of men over 65, and Aortic Dissection (AD) is a life-threatening aortic pathology associated with high morbidity and mortality. Initiators of AAA and AD include smoking and arterial hypertension, whilst key pathophysiological features of AAA and AD include chronic inflammation, hypoxia, and large modifications to the extra cellular matrix (ECM). As it stands, only surgical methods are available for preventing aortic rupture in patients, which often presents difficulties for recovery. No pharmacological treatment is available, as such researchers are attempting to understand the cellular and molecular pathophysiology of AAA and AD. Upregulation of matrix metalloproteinase (MMPs), particularly MMP-2 and MMP-9, has been identified as a key event occurring during aneurysmal growth. As such, several animal models of AAA and AD have been used to investigate the therapeutic potential of suppressing MMP-2 and MMP-9 activity as well as modulating the activity of other MMPs, and TIMPs involved in the pathology. Whilst several studies have offered promising results, targeted delivery of MMP inhibition still needs to be developed in order to avoid surgery in high risk patients.